A Begrudging, Recalcitrant Academic Observes What She's Learning: Distance Learning in Leadership Formation. (July 2014) - Hess, Lisa M.
Abstract Neither advocacy nor condemnation of distance learning, this essay offers observations and critical reflection on four years' longitudinal engagement with distance learning pedagogies for formation in higher theological education. Instead, readers are invited to curiosity, communal‐institutional discernment, and intense ambivalence. Theological, pedagogical, contextual, and ethical concerns are examined, as well as potential opportunities for innovation amidst age‐old practical theological challenges. A moral imperative emerges for those within and outside historic faith traditions, and some plausible impacts on educational and communal life are explored, especially faculty grief.